Guidelines. Developing and implementing a sustainable urban mobility plan. - (:unkn) unknown (My University, 2011)
The EC s Action Plan on Urban Mobility calls for an increase in the take up of sustainable urban mobility planning in Europe. The document introduces the concept of Sustainable Urban Mobility Plans and sets out the steps involved in the preparation of such plans. It is aimed at practitioners in urban transport and mobility as well as other stakeholders who would be involved in the preparation and implementation of Sustainable Urban Mobility Plans. The guidelines presented in this working document focus on the basic description of essential requirements for Sustainable Urban Mobility Plans. They include good practice examples, tools and references that further illustrate the development and implementation of a Sustainable Urban Mobility Plan.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Stadtverkehr; Richtlinie; Fahrradförderung; Projekt; Fahrradinfrastruktur; Nachhaltige Mobilität; Good Practice; Handlungsempfehlung; Implementation